A new Vanilla species from Peninsular Malaysia - Akmal, Raffi; Nur Ashikin, Psyquay Abdullah; Thohirah, Lee Abdullah; Rusea, Goa (2017)
A new species, Vanilla sanguineovenosa R. Go & A. Raffi, from Peninsular Malaysia is described, illustrated, and other aspects of interest discussed. It is so far known from a small population in lower montane forests at Tapah, Perak. A field key to the Peninsular Malaysian taxa, including V. sumatrana is also provided.